2009
DOI: 10.1084/jem.20090560
|View full text |Cite
|
Sign up to set email alerts
|

Aryl hydrocarbon receptor in combination with Stat1 regulates LPS-induced inflammatory responses

Abstract: Toll-like receptor (TLR) signals perform a crucial role in innate immune responses to pathogens. In this study, we found that the aryl hydrocarbon receptor (Ahr) negatively regulates inflammatory responses mediated by lipopolysaccharide (LPS) in macrophages. Ahr was induced in macrophages stimulated by LPS, but not by transforming growth factor (TGF)-β plus interleukin (IL)-6, which can induce Ahr in naive T cells. The production of IL-6 and tumor necrosis factor (TNF)-α by LPS was significantly elevated in Ah… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

24
306
2
2

Year Published

2011
2011
2014
2014

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 365 publications
(345 citation statements)
references
References 36 publications
24
306
2
2
Order By: Relevance
“…AhR inhibited LPS-induced expression of proinflammatory cytokines (for example, IL-6, TNF-a) through suppressing NF-kB transcriptional activity together with STAT1 (ref. 25). Consistently, we found that AhR activation inhibited LPS-mediated pro-IL-1b expression at both the protein and mRNA levels (Fig.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…AhR inhibited LPS-induced expression of proinflammatory cytokines (for example, IL-6, TNF-a) through suppressing NF-kB transcriptional activity together with STAT1 (ref. 25). Consistently, we found that AhR activation inhibited LPS-mediated pro-IL-1b expression at both the protein and mRNA levels (Fig.…”
Section: Discussionsupporting
confidence: 85%
“…For example, various AhR ligands such as TCDD regulate the differentiation of Treg cells and Th17 cells 26,[32][33][34] , and modulate Th1/Th2 balance 35 . AhR in combination with STAT1 negatively regulates proinflammatory cytokine production by inhibiting NF-kB activation in macrophages after LPS stimulation 25 . AhR knockout mice are hypersensitive to LPS-induced septic shock, mainly due to macrophage dysfunction 36 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that IL-6 is produced by several types of cells, including antigen-presenting cells such as macrophages and dendritic cells, we cannot exclude the possibility that expression of the miR-132/212 cluster in these cells is important for EAE development. Therefore, it is also necessary to gain an understanding of how the miR-132/212 cluster regulates the immune system in various types of immune cells, such as T cells, macrophages, and dendritic cells, by conducting research similar to our study of AHR in these immune cells (7,39,40). For instance, we recently found that AHR deficiency in peritoneal macrophages results in failure to induce the miR-132/212 cluster in response to LPS.…”
Section: Discussionmentioning
confidence: 99%
“…AhR participates in the differentiation of effector and regulatory T cells as a result of AhR activation in T cells and dendritic cells (DCs) [1]. In addition, AhR in macrophages modulates their activation by lipopolysaccharide (LPS) [5,6] but the molecular mechanisms involved are not clearly understood. A study by Puccetti and colleagues describes a pathway by which AhR limits the inflammatory response to LPS [7].…”
mentioning
confidence: 99%